Antibiotic resistance of urinary tract pathogens and rationale for empirical antibiotic therapy in children with urinary tract infection - Rasheed Alkhateeb, Nazdar Ezzaddin (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Increased antimicrobial resistance of urinary tract pathogen is a matter of global public health concern. The purpose of this study was to identify the most common bacteria causing urinary tract infection and detection of antibiotics susceptibility of isolates to evaluate the options for empirical antibiotic therapy in children with urinary tract infection in Erbil city. Methods: This study was conducted in Raparin Teaching Hospital on urine samples culture results over a one year period retrospectively. Hospital microbiology recording book was screened. Throughout the study period, 1622 children suspected to have urinary tract infection were investigated for urine culture. Disc diffusion technique according to clinical and laboratory standards institute (CLSI) was performed to determine antibiotics susceptibility of isolated bacteria species. Results: Of 1622 children with suspected urinary tract infection, 514(31.69%) had a positive bacterial culture that included 104 males and 410 females. The most common isolates were E Coli (54.1 %), Staphylococcus (19.1%) and Proteus (12.5%). The most effective antibiotics against isolated pathogens were imipenem, ciprofloxacin and nitrofurantoin with sensitivity rate 95.2%, 78.8% and 74.1% respectively. Conclusion: This study revealed that E. coli and staphylococcal strains were the most frequent isolated pathogens among our population; empirical antibiotic selection should be based on the knowledge of the local prevalence of bacterial organism and antibiotic sensitivity.